CONTRADICTION OF THE RIGHT TO DENY OF NOTARY WITH THE OBLIGATION TO REPORTING FOR THE PREVENTION OF MONEY LAUNDERING - Ida Ayu Ide Dinda Paramita; I Nyoman Gede Sugiartha; I Made Pria Dharsana (NOTARIIL Jurnal Kenotariatan, 2022)
The purpose of this study is to examine the contradiction regarding the Principles of Recognizing Service Users (PMPJ) with the provisions of maintaining the confidentiality of the Deed by a Notary and to examine the limitations regarding the obligation of a Notary to keep the contents of the Deed secret with the obligation to report the Deed related to alleged money laundering. The research type used is normative legal research, with a statutory approach and a conceptual approach. The technique of collecting legal materials uses identification techniques and snowball techniques. The results show that based on Law Number 12 of 2011 concerning the Establishment of Legislation and the principle of lex superior derogate legi inferior. Moreover, between UUJN.P and Government Regulation Number 43 of 2015 concerning Plaintiff in the Prevention and Eradication of the Crime of Money Laundering, which is implementing regulations of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering, the obligation to keep the data of service users cannot be disclosed by a Notary.